Experimental Investigation on Uniaxial Unconfined Compressive Properties of Ice on Asphalt Pavement Surface - Luo, Wei; Dan, Hancheng; Zeng, Runzhong; Rong, Yao; Xie, Dian (Frontiers in Materials, 2020)
Mechanical deicing is a method to remove the ice on the pavement surface, and the ice strength directly affects the difficulty and effectiveness of the mechanical deicing. This paper aims to investigate the compression strength of ice to facilitate the deicing equipment to crush ice. In this paper, a large-scale freezing laboratory is employed to simulate low temperature environment, and the uniaxial unconfined compressive tests of artificial fresh-water ice under different temperature conditions are carried out through the uniaxial loading system. The compressive strength and modulus of ice are obtained when the substrate is asphalt pavement. The test result shows that the ice compressive strength and modulus respectively distribute from 0.36 MPa to 3.67 MPa and 11.7 MPa to 359.1 MPa when ice temperature varies from -0.7℃ to -7.5℃. The relations between ice temperature and compressive strength are approximately in linear manner, while the relation of compressive modulus and ice temperature shows good power function and exponential relationships respectively when ice temperature ranges from -8℃ to -5℃ and from -5℃ to 0℃. Furthermore, the failure mechanism of ice under relatively lower temperature is due to the development of cut-through cracks inside the ice. The failure mode divides into shear failure and ductile failure and the failure ice is mainly composed of large ice strips and bulks. For the ice with relatively higher temperature especially the ice close to melting point temperature, the ice failure mode is compressive and ductile, and the failure ice is mainly composed of granular ice crystals.